Unlocking the ‘Eskimo Secret’: Defence Science in the Cold War Canadian Arctic, 1947–1954 - Wiseman, Matthew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
Between 1947 and 1954, medical scientists in Canada received support from federal and independent agencies to conduct a series of comparative biochemical studies on Inuit and white “test subjects.” Originally conceived from a racialized intrigue in defining the vascular characteristics of cold tolerance, the Canadian defence establishment absorbed the research with the intent to apply the findings to military service work in the North. Potentially unlocking the “Eskimo” secret to cold-weather acclimatization meant scientists could devise a screening process for selecting male white bodies for Arctic service. The research took place within the edifice of colonial science, but unlike wider postwar perceptions of the Indigenous body, this article presents the concept of biological appropriation to explore the perceived value of Inuit physiology to northern defence. Interpreting experiential research on Inuit as distinct from cultural assimilation provides a broader interpretation of postwar Arctic policy, and helps discern an understudied yet important episode of the Cold War sciences in Canada.